An Insight of Smartphone-Based Lifelogging Research: Issues, Challenges, and Research Opportunities: Insight of Smartphone-Based Lifelogging Research - Ali, Shaukat; Khusro, Shah; Khan, Akif; Khan, Inayat; Solheria, Salman Faiz (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The technological advancements have turned smartphone into a de-facto lifelogging device and fostered smartphone-based lifelogging (SBL) research as a mainstream activity. A SBL system can capture and store information about peoples' daily life activities, behaviours, interactions, contexts, etc., into a comprehensive personal lifelogs. The smartphone-based personal lifelogs can be of interest to the different stakeholders including users, information sciences researchers, and policies/decisions makers in governments and organizations because of the availability of information for solving different real-world problems (e.g., memory augmentation, medicine and health care, business and commerce, government policy making, society development, etc.), which would otherwise be impossible. Despite of potential advantages, SBL research is in its early stages and has several issues and challenges, which impedes its large-scale adaptation. Therefore, more research efforts are needed in the SBL domain. This paper is aimed to provide an insight review of SBL research and highlight several issues, challenges, and research opportunities. Firstly, the smartphone is demonstrated as a de-facto lifelogging device and available SBL research is analysed to highlight research shortcomings and gaps. Secondly, a generalized architecture for SBL systems is presented to unify and accelerate the research and development efforts. Lastly, several issues and challenges are highlighted, which could be turned into potential research opportunities. This paper can be a valuable resource for new researchers to find research topics to contribute and explore the SBL research area.